2022
DOI: 10.1007/s40688-022-00420-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term English Learners: Untangling Language Acquisition and Learning Disabilities

Abstract: Students who have remained classified as English Learners (ELs) for more than six years are often labeled “Long-term English Learners” (LTELs). The present study examined the English Language Development (ELD) test scores and demographic information in a group of 560 students identified as LTELs. Despite assumptions that these students are still learning English, results showed many students who are labeled LTELs exhibited advanced English skills, especially on measures of expressive and receptive oral languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This indicates a progressive understanding and growing awareness of the importance of English language proficiency as students progress through their high school years. This finding aligns with previous research on non-native English speakers, which suggests that students in high school settings often perceive improvements in their English language skills through coursework and social interaction, and that tends to increase the higher the grade level (Rhinehart et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates a progressive understanding and growing awareness of the importance of English language proficiency as students progress through their high school years. This finding aligns with previous research on non-native English speakers, which suggests that students in high school settings often perceive improvements in their English language skills through coursework and social interaction, and that tends to increase the higher the grade level (Rhinehart et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that as students progress through their high school years, they develop a more favourable view of their English language competence and become more aware of their strengths in the various language domains. This reiterates the conclusions drawn from earlier research, which indicate that students tend to be content with their language proficiency and value English as a Second Language courses (Rhinehart et al, 2022). Furthermore, this consistency is in line with another study that revealed students rating themselves as having "good" English language skills in areas such as understanding teachers' instructions, speaking in class, and writing in English, with the ratings progressively improving with higher grade levels (Kasuma et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…However, this delay could also prevent ELs who do in fact have dyslexia (i.e., true positives captured by the screener) from receiving the most effective reading interventions for students with dyslexia. Further, a nontrivial number of students remain classified as ELs beyond elementary school (Rhinehart et al, 2022), and screening should not be delayed to that extent in a child's schooling. Some research on screening ELs for LDs like dyslexia suggests that students should be assessed on their reading skills in their first language.…”
Section: Dyslexia and English Learnersmentioning
confidence: 99%
“…Other high-quality work has explored the intersection of culture and developmental linguistic practices. Still other work explores the role of policies related to ELL reclassification and implications for long-term ELL status (Rhinehart et al, 2022). To our knowledge, research has not explored development processes in the social-emotional domain that contribute to understanding why students linger as ELLs with continued challenges in reading.…”
Section: Future Directions: Leveraging Communities' Cultural Assets A...mentioning
confidence: 99%
“…Especially in the midst of the COVID-19 pandemic, virtual connections made possible access to mental and physical health supports. For example, young adults reported using social media and digital mental health tools to alleviate depression and anxiety (Rideout et al, 2021). At the same time, many researchers have found widespread evidence of adverse effects of smartphone, social media, and other technology on adolescent identity development, affect, mental health, social connectedness, empathy, attention, and sociocognitive reflective capacities (e.g., Alter, 2017; Gardner & Davis, 2013; Steiner-Adair & Baker, 2013; Twenge et al, 2018), especially for girls (Twenge et al, 2022) and racial-ethnic minority adolescents (Weinstein et al, 2021).…”
Section: Learning 8: Digital Versus Print Readingmentioning
confidence: 99%